1994
DOI: 10.1128/aem.60.8.3011-3019.1994
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Growth, and Metabolism of an Obligately Anaerobic, Selenate-Respiring Bacterium, Strain SES-3

Abstract: A gram-negative, strictly anaerobic, motile vibrio was isolated from a selenate-respiring enrichment culture. The isolate, designated strain SES-3, grew by coupling the oxidation of lactate to acetate plus CO2 with the concomitant reduction of selenate to selenite or of nitrate to ammonium. No growth was observed on sulfate or selenite, but cell suspensions readily reduced selenite to elemental selenium (Seo). Hence, SES-3 can carry out a complete reduction of selenate to Seo. Washed cell suspensions of selena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(121 citation statements)
references
References 45 publications
2
116
2
Order By: Relevance
“…The influence of alternate electron acceptors on reduction of and on growth was variable ( Table 1). Respiration 2Ϫ SeO 4 has been identified as a mechanism by which bacteria reduce Se oxyanions [19,25,26]. As noted, previous work in our laboratory with SLD1a-1 has shown that reduction of oc-2Ϫ SeO 4 curs via terminal reductase(s) as a result of respiration [9].…”
Section: ϫ 2ϫmentioning
confidence: 84%
“…The influence of alternate electron acceptors on reduction of and on growth was variable ( Table 1). Respiration 2Ϫ SeO 4 has been identified as a mechanism by which bacteria reduce Se oxyanions [19,25,26]. As noted, previous work in our laboratory with SLD1a-1 has shown that reduction of oc-2Ϫ SeO 4 curs via terminal reductase(s) as a result of respiration [9].…”
Section: ϫ 2ϫmentioning
confidence: 84%
“…In the case of S. maltophilia, NO 3 should not interfere with the reduction of either Se oxyanion since the organism cannot respire NO 3 -(data not shown), but additional studies are scheduled to determine if the organism displays a negative physiological response to high NO 3 concentrations. Of additional importance, S. maltophilia can reduce SeO 4 2and SeO 3 2under microaerophilic conditions; in contrast, the majority of work on Se-reducing bacteria has focused on organisms that require strict anaerobicity (Gerhardt et al, 1991;Tomei et al, 1992;Macy, 1994;Oremland et al, 1994;Rege et al, 1999). Because bioreactor influent will contain O 2 , the ability of S. maltophilia to grow in the presence of O 2 and rapidly reduce Se oxyanions in the presence of low levels of O 2 could be extremely advantageous.…”
Section: Reduction Of Selenate and Selenitementioning
confidence: 99%
“…Recently, some bacterial strains which can effectively reduce selenate into selenite or elemental selenium have been reported [2,[6][7][8]12]. They are all gram-negative bacteria.…”
Section: Flavobacterium Okeanokoites Saccharococcus Thermophilus Macrmentioning
confidence: 99%
“…During the selenate-and selenite-reduction, cell growth was observed. Like Thauera selenatis [5,6] and Sulufurospirillum barnesii strain SES-3 [3,4,12], SF-1 grew with selenate or selenite as an electron acceptor and lactate as an electron donor for the anaerobic respiration.…”
Section: Selenate and Selenite Reduction Testsmentioning
confidence: 99%